Green taxes and subventions - Roncz, Judit (НТУ "ХПИ", 2009)
In the recent decade all EU member states try to cover their increasing energy demand with renewable energy resources. It is not only incited by EU Directives but also several complex economic- and environmental benefits. We can also state that there is no harmonized green energy subvention in the EU, the member states has different practices. In this study my goal is to summarize and to analyze the efficiency of the current legislations and supportive instruments.

В последнее десятилетие все государства-члены ЕС пытаются покрыть свое увеличивающееся энергопотребление ресурсами возобновляемого источника энергии. Это не только приписывается Директивами ЕС, но и несколькими экономическими комплексами – а также экологическими льготами. Можно также заявить, что нет никакой согласованной зеленой дотации энергии в ЕС, государства-члены ЕС имеют свои различные методы. Цель статьи состоит в подведении итогов и анализе эффективности действующего законодательства.